Effects of dipeptidyl peptidase 4 inhibition on inflammation in atherosclerosis: A 18F-fluorodeoxyglucose study of a mouse model of atherosclerosis and type 2 diabetes - Jenni Virta; Sanna Hellberg; Heidi Liljenbäck; Mia Ståhle; Johanna M.U. Silvola; Jenni Huusko; Mirva Söderström; Juhani Knuuti; Pirjo Nuutila; Seppo Ylä-Herttuala; Maria F. Gomez; Anne Roivainen; et al. (Elsevier Ireland Ltd, 2022)
Background and aims: Dipeptidyl peptidase 4 (DPP-4) inhibitors have anti-inflammatory and atheroprotective effects. We evaluated the effects of the DPP-4 inhibitor linagliptin on atherosclerotic plaque and hepatic inflammation using histology and 2-deoxy-2-[18F]-fluoro-d-glucose (18F-FDG), a positron emission tomography tracer of inflammation, in a mouse model of hypercholesterolemia and type 2 diabetes.
Methods: Igf2/Ldlr-/-Apob100/100 mice were fed a high-fat diet (HFD) for 8 weeks and then randomly allocated to receive HFD (n = 14), or HFD with added linagliptin (n = 15) for additional 12 weeks. Five mice fed a chow diet were studied as an additional control. At the end of the study, glucose tolerance, aortic and liver uptake of 18F-FDG, and histology were studied.
Results: Mice in linagliptin and HFD groups had similar fasting glucose concentrations, but linagliptin improved glucose tolerance. Aortas of linagliptin and HFD groups showed advanced atherosclerotic plaques with no difference in the mean intima-to-media ratio or number of macrophages in the plaques. Autoradiography showed similar 18F-FDG uptake by atherosclerotic plaques in linagliptin and HFD groups (plaque-to-wall ratio: 1.7 ± 0.25 vs. 1.6 ± 0.21; p = 0.24). In the liver, linagliptin reduced the histologic inflammation score but had no effect on 18F-FDG uptake. Compared with chow diet, uptake of 18F-FDG was similar in the aorta, but higher in the liver after HFD.
Conclusions: Linagliptin therapy improved glucose tolerance and reduced hepatic inflammation but had no effect on plaque burden or atherosclerotic inflammation, as determined by histology and 18F-FDG uptake, in atherosclerotic mice with type 2 diabetes.